Answer:
Vertical asymptotes
Horizontal asymptote
![y=3](https://img.qammunity.org/2020/formulas/mathematics/high-school/bz4oxcswmw3r7gvwn866nuoh3alxt85uy3.png)
Explanation:
We have the function
and we want to find its asymptotes.
First we find their vertical asymptotes.
To do this we must factor the denominator of the expression.
![x ^ 2 + 3x-10](https://img.qammunity.org/2020/formulas/mathematics/middle-school/teuoajnm3yer9wxkncx2ea72rame6t3ofs.png)
We must look for two numbers that when adding them obtain 3, and when multiplying those same numbers, obtain -10.
The searched numbers are 5 and -2
Then the factors are:
![(x + 5)(x-2)\\\\x ^ 2 + 3x-10 = (x + 5)(x-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/50qyj2bf0vgt1nxynk8r83xsa7cwmz2ptg.png)
Since the division between zero is not defined then when x tends to -5 the function tends to infinity and when x tends to 2 the function tends to infinity.
So the vertical asymptotes will be the straight lines:
The horizontal asymptote is calculated as:
![\lim_(x \to\infty)f(x)\\\\= \lim_(x \to\infty)(3x ^ 2-2x-1)/(x ^ 2 + 3x-10)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vf6egqkuiycuvg08bnphle6w5ufq3ucgr8.png)
The highest exponent of the function is 2. Then the terms with exponents less than 2 tend to zero
![\lim_(x \to\infty)(3x ^ 2-2x-1)/(x ^ 2 + 3x-10) =\lim_(x \to\infty)(3x ^ 2)/(x ^ 2)\\\\ = \lim_(x \to\infty)(3)/(1) = 3\\\\](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ohgo8a1olj5is635dnvsb9wdw7vz8ul6l8.png)
Then
![\lim_(x \to\infty)f(x)=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mu9l63fbmo75hriuqrkgy1tqipxwtz03g2.png)
Therefore the horizontal asymptote is:
![y=3](https://img.qammunity.org/2020/formulas/mathematics/high-school/bz4oxcswmw3r7gvwn866nuoh3alxt85uy3.png)
Observe the attached image